Comorbidity is an independent prognostic factor in patients with advanced‐stage diffuse large B‐cell lymphoma treated with R‐CHOP: a population‐based cohort study. (7th February 2014) - Wieringa, Andre; Boslooper, Karin; Hoogendoorn, Mels; Joosten, Peter; Beerden, Tim; Storm, Huib; Kibbelaar, Robby E.; Veldhuis, Gerrit J.; van, Harmen; van, Bastiaan; Kluin‐Nelemans, Hanneke C.; Veeger, Nic J. G. M.; et al.
Summary An observational population‐based cohort study was performed to investigate the role of comorbidity on outcome and treatment‐related toxicity in patients with newly diagnosed advanced‐stage diffuse large B‐cell lymphoma (DLBCL) treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone). Data for the clinical characteristics of 154 patients (median age 69 years), including Charlson Comorbidity Index (CCI), treatment, toxicity and outcome were evaluated. Forty‐five percent of the patients had an International Prognistic index ≥3 and 16% had a CCI ≥2. The planned R‐CHOP schedule was completed by 84% and 75% reached complete remission (CR). In those with CCI ≥2, 67% completed treatment with 46% CR. In patients with a CCI <2, overall survival (OS) after 1, 2 and 5 years was 84%, 79% and 65% respectively and it was 64%, 48% and 48% for those with CCI ≥2. Grade III/IV toxicity was documented in 53%, most frequently febrile neutropenia (27%) and infections (23%). In multivariate analysis CCI ≥2 and IPI ≥3 were independent risk indicators for OS and grade III/IV toxicity. In conclusion, comorbidity is an independent risk indicator for worse OS in patients with advanced DLBCL treated with R‐CHOP by interference with intensive treatment schedules and more grade III/IV toxicity. Future studies are warranted to determine the optimal treatment approach in patients with significant comorbidities.